ANALISIS FLAVONOID TOTAL EKSTRAK ETANOL DAUN SELIGI (PHYLLANTHUS BUXIFOLIUS MUELL. ARG) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Sari, Diah Kemala; Hastuti - Politeknik Kesehatan Bhakti Mulia, Siwi (IJMS - Indonesian Journal on Medical Science, 2020)
Abstract: Seligi plants (Phyllanthus buxifolius Muell. Arg) have long been empirically used by the community as pain medications in sprained joints and to treat rheumatism. Apart from being anti-pain, seligi leaves are also known to be used as antioxidants, antipyretics and anti-inflammatory. Various benefits of seligi leaves indicate that seligi leaves contain large flavonoids, the more benefits produced by a plant, the greater the flavonoid content contained by these plants. This study aims to analyze the total flavonoid levels contained in the ethanol extract of seligi leaves. Isolate the extract using maceration methods. Determination of total flavonoid levels of ethanol extract of seligi leaves using a comparison of quercetin with a series of concentrations of 50, 100, 200, 300, 400 ppm with a wavelength of 480 nm. absorbance values were measured by UV-Vis spectrophotometer. The absorbance value was analyzed using a linear regression equation so that the total flavonoid levels obtained from the ethanol extract of seligi leaves. The results obtained by quercetin concentration from each series of concentrations of 50 ppm (0.165), 100 ppm (0,250), 200 ppm (0.362), 300 ppm (0.468) and 400 ppm (0, 893), and total flavonoid extract levels ethanol leaves seligi at 13, 70%. The results obtained by the total flavonoid levels of ethanol extracts of seligi leaves were (13.86 ± 1, 27)%.Keywords: UV-Vis spectrophotometry, Seligi, Phyllanthus buxifolius, total flavonoid. Abstrak: Tanaman seligi (Phyllanthus buxifolius Muell. Arg) sejak lama secara empiris digunakan masyarakat sebagai obat nyeri pada sendi terkilir dan untuk mengobati rematik. Selain sebagai anti nyeri, daun seligi juga diketahui dapat digunakan sebagai antioksidan, antipiretik dan antiinflamasi. Berbagai manfaat dari daun seligi menandakan bahwa daun seligi mengandung flavonoid yang besar, semakin banyak manfaat yang dihasilkan oleh suatu tanaman, maka semakin besar pula kandungan flavonoid yang dikandung oleh tanaman tersebut. Penelitian ini bertujuan untuk menganalisis kadar flavonoid total yang terkandung dalam ekstrak etanol daun seligi. Isolasi ekstrak menggunakan menggunakan metode maserasi. Penentuan kadar flavonoid total ekstrak etanol daun seligi menggunakan pembanding kuersetin dengan seri konsentrasi 50, 100, 200, 300, 400 ppm dengan panjang gelombang 480 nm. nilai absorbansi diukur dengan spektrofotometer UV-Vis. Nilai absorbansi dianalisis menggunakan persamaan regresi linier sehingga didapatkan hasil kadar flavonoid total ekstrak etanol daun seligi. Hasil penelitian diperoleh konsentrasi kuersetin dari masing-masing seri konsentrasi 50 ppm (0,165), 100 ppm (0,250), 200 ppm (0,362), 300 ppm (0,468) dan 400 ppm (0, 893), dan kadar flavonoid total ekstrak etanol daun seligi sebesar 13, 70 %. Hasil penelitian diperoleh kadar flavonoid total ekstrak etanol daun seligi sebesar (13,86 ± 1, 27)%.Kata kunci: Spektrofotometri UV-Vis, Seligi, Phyllanthus buxifolius, Flavonoid total